The Activities of the Coroplastic Studies Interest Group - Erica Angliker (Les Carnets de l’ACoSt)
The Coroplastic Studies Interest Group (CSIG) held a meeting at the 121st Annual Meeting of the Archaeological Institute of America and the Society for Classical Studies in Washington, DC (January 3–6, 2020).